Modifying Effect of Anthocyanin from Purple Sweet Potatoes on Visceral Fat Tissue Inflammation and Liver Oxidative Stress in Psychological Stress-Induced Mice: Purple Sweet Potatoes on Psychological Stress - Nia Kurnianingsih; Dian Artamevia; Antania Kashira Winarta; Andini Putri Wulandari; Dian Hasanah; Edwin Widodo; Retty Ratnawati (Journal of Tropical Life Science, 2023)
Psychological stress generates inflammation and oxidative stress in various tissues. Visceral fat as the target site of inflammation is then correlated with stress-induced obesity. Redox imbalance following inflammation also has prominent impacts on hepatic tissue. Therefore, the development of anti-inflammatory and antioxidant properties from plant bioactive compounds is necessary to be investigated. Anthocyanin (ANC) from various plants is previously described as a powerful anti-inflammatory and antioxidant even though its effect in psychological stress remains underexplored. Purple sweet potatoes (PSP) has ANC as its natural pigment. Previous studies revealed the potential effect of ANC from PSP on behavior and an antidepressant candidate. Thus, this study was purposed to determine the effect of ANC from PSP on inflammation and oxidative stress in visceral fat and hepatic tissue respectively. A total of 25 adult male BALB/c mice were assigned into groups of control, stress, stress+ANC 10 mg/kgBW, stress+ANC 20 mg/kgBW and stress+ANC 40 mg/kgBW. Restraint stress was applied 2 hours/day for 14 days. Enzyme-linked immunoassay (ELISA) was conducted to measure level of IL-6 and IL-10 in visceral fat as well as SOD and MDA from hepatic tissue. The results demonstrated that the supplementation of ANC reduces the level of IL-6 cytokine (p=0.005), tends to increase IL-10 (p=0.612), reduces hepatic SOD (p=0.03), and does not significantly affect the level of hepatic MDA (p=0.432). Both ratios of IL-6/IL-10 and SOD/MDA were reduced following ANC administration. Total ANC extracts are suggested to have a potential role of resisting inflammation and oxidative stress in the psychologically stressed model. Further studies are necessary to evaluate the benefits of ANC from PSP in other peripheral organs under psychological stress exposure.